Sleep quality disorders among the people of old and presenile age - Podhorecka, Marta; Cytarska, Magdalena; Gębka, Dominika; Perkowski, Radosław; Jaroch, Alina; Siedlecka–Główczewska, Emilia; Sokołowski, Remigiusz; Radzińska, Michalina; Zukow, Walery; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2017)
<span style="font-size: 12.0pt; line-height: 107%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-GB">According to the newest research over the half of geriatric population suffers from sleep disorders. Lowered quality of sleep has got a negative influence on biopsychosocial functioning of an individual. The aim of the study was to define the magnitude of the problem of sleep quality disorders occurrence in the elderly. The research for the study was carried out by means of anonymous survey which consists of two questionnaires: The Pittsburgh Sleep Quality Index (PSQI) and a survey constructed for the sake of the study. 100 people took part in the study and the survey was aimed at people over the age of 50. The research showed that over one fifth of the subjects assess their sleep as rather bad and significant correlations between lengthening the time needed to fall asleep and waking up at night or before dawn and the lack of energy.